1994
DOI: 10.1111/j.1524-4725.1994.tb03200.x
|View full text |Cite
|
Sign up to set email alerts
|

Healing Impairment of Open Wounds by Skin Irradiation

Abstract: Radiation of skin results in slower healing of open wounds, and provides an in vivo system for evaluation of topical dressings and growth factors in radiation-impaired wounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
2
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 21 publications
1
23
2
1
Order By: Relevance
“…Results obtained from previous studies have demonstrated that prior irradiation with x-ray doses of 20 Gy caused a significant delay in the rate of wound healing by day 7 when compared with the non-x-ray-irradiated control [18,30]; Bernstein et al [29] also reported similar findings. The impaired wound-healing model used in the present study showed a significantly extended proliferative phase during the wound-healing process, whereas at the inflammatory and remodelling phases this delay was not found to be significant.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Results obtained from previous studies have demonstrated that prior irradiation with x-ray doses of 20 Gy caused a significant delay in the rate of wound healing by day 7 when compared with the non-x-ray-irradiated control [18,30]; Bernstein et al [29] also reported similar findings. The impaired wound-healing model used in the present study showed a significantly extended proliferative phase during the wound-healing process, whereas at the inflammatory and remodelling phases this delay was not found to be significant.…”
Section: Discussionsupporting
confidence: 75%
“…Additionally, to stimulate pathologic wounds similar to those found clinically (e.g., in elderly and diabetic patients), an impaired wound-healing model is necessary. Such an impaired wound-healing model can be induced through x-ray irradiation; although its effect has been found to be dose-dependent [27], it has been reported recently that x-ray irradiation of a single 20-Gy dose to the skin delays wound healing by 7 days [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…It stimulates collagen and proteoglycan synthesis. pDGF is involved in all stages of wound healing and influences the growth and the function of various mesenchymal cells (60).…”
Section: Vascular Endothelial Growth Factor (Vegf)mentioning
confidence: 99%
“…BERNSTEIN et al 4 , em 1994, apresentaram estudo mostrando que seqüelas da radiação ionizante são decorrentes da pobre reparação da ferida.…”
Section: Introductionunclassified